Study of soil-plant transfer of 226Ra under greenhouse conditions - Soudek, Petr; Petrová, Sárka; Benesová, Dagmar; Kotyza, Jan; Vágner, Martin; Vanková, Radomíra; Vanek, Tomás (Journal of environmental radioactivity, 2010)
A soil-plant transfer study was performed using soil from a former uranium ore processing factory in South Bohemia. We present the results from greenhouse experiments which include estimates of the time required for phytoremediation. The accumulation of (226)Ra by different plant species from a mixture of garden soil and contaminated substrate was extremely variable, ranging from 0.03 to 2.20 Bq (226)Ra/g DW. We found differences in accumulation of (226)Ra between plants from the same genus and between cultivars of the same plant species. The results of (226)Ra accumulation showed a linear relation between concentration of (226)Ra in plants and concentration of (226)Ra in soil mixtures. On the basis of these results we estimated the time required for phytoremediation, but this appears to be too long for practical purposes.
Keywords: rostliny; Lupinus; Greenhouse Effect; skleníkový efekt; Plants; Biodegradation, Environmental; Soil; radium; biodegradace; půda; Radium